On the shop-floor: ten years at Ford,Idangatye ngobusuku - Cilibe, Mpumelelo (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
My autobiographical novella covers a period of my life between 1974 and 1984, when I worked at the Ford Motor company Struandale Assembly plant in Port Elizabeth. This period predated the formation of NUMSA (the National Union of Metal Workers of South Africa) and COSATU - it was a time when automobile industry workers broke away from the race- based unions to form MACWUSA (Motor Assemblers and Component Workers Union of SA). Around the same time Rev Leon Sullivan was putting pressure on US companies, including Ford, to move away from apartheid labour practices. As quite an angry young man influenced by the Black Consciousness movement, I got deeply involved in union activities mainly for my own survival, and as a personal reaction to racism in the workplace. The story is told in a realist style, with many anecdotal detours giving the flavour of life in New Brighton in the 1980s. Important influences have been Bloke Modisane's autobiography, Blame Me on History and Studs Terkel's interviews of Ford plant workers and management in his book Working.,Growing up in New Brighton gave me so many stories that had never been written before but that were told person to person by the residents of my neighbourhood. Some of the tales in this collection are based on such stories. Others are stories that are reminiscent of childhood while growing up with an elder brother. I take the inspiration from different books that are in line with the stories that I am writing: collections of Extreme Fiction - Fabulists and Formalists that were edited by Robin Hemley and Michael Martone and The Best Bizarro Fiction of the Decade edited by Jeremy Robert Johnson and Cameron Pierce. Some stories by L.L. Ngewu and L.S. Ngcangata, and a novellette by P.T. Mtuze, Alitshoni Lingaphumi, also bring much influence as they reveal suffering in the lives of black people who endured forced removals, and other situations that are of interest to build my stories on.,Le ngqokolela yamabali iqulathe amabali asekelwe kumabali endandiweva ebaliswa ebuntwaneni bam ndisakhula. Amanye amabali angeenkumbulo zasebuntwaneni ngethuba ndandikhula nomkhuluwa wam ongasaphiliyo. Ifuthe lokuwaqamba ndilifumene kwiincwadi zababhali abanje ngabo bafumaneka kwiingqokolela ezihlelwe nguRobin Hemley no Michael Martone kwincwadi ethi Extreme Fiction - Fabulists and Formalists, noJeremy Robert Johnson enoCameron Pierce kwingqokolela ethi, The Best Bizarro Fiction of the Decade. Amanye amabali abenefuthe ndiwafumene kwiincwadi zooP.T. Mtuze, kwinovella yakhe ethi Alitshoni Lingaphumi, nakwezoL.L. Ngewu noL.S. Ngcangatha apho babalisa ngobomi basekuhlaleni ngexesha abantu babedudulwa befuduswa ngetshova ukususwa kwiindawo zabo zokuhlala.,This thesis is presented in two parts: English and isiXhosa
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Autobiographical fiction, South African (English) 21st century; Xhosa fiction 21st century; Short stories, Xhosa 21st century